2000
DOI: 10.2337/diacare.23.10.1455
|View full text |Cite
|
Sign up to set email alerts
|

Intervention study for smoking cessation in diabetic patients: a randomized controlled trial in both clinical and primary care settings.

Abstract: Abbreviations: CHD, coronary heart disease; FTND, Fagerström Test for Nicotine Dependence; NRT, nicotine replacement therapy.A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. Intervention Study for Smoking Cessation in Diabetic PatientsA randomized controlled trial in both clinical and primary care settingsOBJECTIVE -To evaluate the effectiveness of a nurse-managed smoking cessation intervention in diabetic patients. RESEARCH DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
92
3
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 21 publications
10
92
3
4
Order By: Relevance
“…In patients with diabetes, training primary care staff in motivational interviewing led to a threefold increase in quit rates in the intervention group (20%) compared to controls (7%) [52]. Another study showed that training diabetes nurses in smoking cessation could significantly increase quit rates (17% versus 2.3%) [53]. In COPD patients, a Cochrane review (five RCTs; two, high quality) concluded, behavioural and pharmacological interventions combined are superior to usual care or behavioural intervention alone in achieving sustained abstinence [54].…”
Section: Effectiveness and Cost-effectivenessmentioning
confidence: 96%
“…In patients with diabetes, training primary care staff in motivational interviewing led to a threefold increase in quit rates in the intervention group (20%) compared to controls (7%) [52]. Another study showed that training diabetes nurses in smoking cessation could significantly increase quit rates (17% versus 2.3%) [53]. In COPD patients, a Cochrane review (five RCTs; two, high quality) concluded, behavioural and pharmacological interventions combined are superior to usual care or behavioural intervention alone in achieving sustained abstinence [54].…”
Section: Effectiveness and Cost-effectivenessmentioning
confidence: 96%
“…The effectiveness of smoking cessation interventions in primary care has been demonstrated through randomized controlled trials in both the general population and among people with diabetes. [12][13][14]27 However, few studies have examined whether such interventions have a differential impact across socioeconomic and ethnic groups and whether such an effect contributes to health inequalities. 12 We found no evidence to suggest that pay-for-performance incentives increased variation in support for smokers and smoking rates 29 A recent British study found that the prevalence of smoking among white Europeans with diabetes (men, 22.2%; women, 20.0%) was similar to the prevalence in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 11% of the smokers agreed to participate and were randomized into intervention or control groups; 5% were non-smokers after six months in a structured behaviour therapy anti-smoking programme and 16% in the control group receiving anti-smoking advice given once by a physician. In a Spanish study, diabetes patients from both primary care and two hospitals were initially invited to participate in a general lifestyle study [19]. After a structured interview with a nurse, 280 patients were randomized to an experimental or control group.…”
Section: Discussionmentioning
confidence: 99%